Users discourses about primary health care professionals in rural Bangladesh - Hasan, Md. Kamrul; Conn, Cath; Wilson, Kaisa (© 2014 Department of Public Health, School of Public Health and Psychosocial Studies, Auckland University of Technology, 2016)
This article was published in the AUT's Public Health Bulletin [© 2014 Department of Public Health, School of Public Health and Psychosocial Studies, Auckland University of Technology] and the definite version is available at : http://www.aut.ac.nz/__data/assets/pdf_file/0004/512977/Hasan-Conn-and-Wilson-2014-bulletin.pdf The article website is at: http://www.aut.ac.nz/study-at-aut/study-areas/health-sciences/Public-Health/research/auts-public-health-bulletin